Bioaccumulation and biochemical responses in the peppery furrow shell Scrobicularia plana exposed to a pharmaceutical cocktail at sub-lethal concentrations - Chiara Trombini; Julia Kazakova; Mercedes Villar-Navarro; Miriam Hampel; Rut Fernández-Torres; Miguel Ángel Bello-López; Julián Blasco (Ecotoxicology and Environmental Safety, 2022)
Pharmaceutical drugs in the aquatic medium may pose significant risk to non-target organisms. In this study, the potential toxicity of a mixture of three compounds commonly detected in marine waters (ibuprofen, ciprofloxacin and flumequine) was assessed, by studying bioaccumulation, oxidative stress and neurotoxicity parameters (catalase CAT, superoxide dismutase SOD, glutathione reductase GR, glutathione S-transferase GST, lipid peroxidation LPO, glutathione peroxidase GPX, metallothionein MT and acetylcholinesterase AChE) in the clam Scrobicularia plana. Temporal evolution of selected endpoints was evaluated throughout an exposure period (1, 7 and 21 days) followed by a depuration phase. The accumulation of all drugs was fast, however clams showed the ability to control the internal content of drugs, keeping their concentration constant throughout the exposure and reducing their content after 7 days of depuration. The induction of biochemical alterations (SOD, CAT, LPO, MT, AChE) was observed in gills and digestive gland probably related to an imbalance in the redox state of clams as a consequence of the exposure to the drug mixture. These alterations were also maintained at the end of the depuration week when the high levels of SOD, CAT, GST and LPO indicated the persistence of oxidative stress and damage to lipids despite the fact that clams were no longer exposed to the mixture.